2019
DOI: 10.7717/peerj.6561
|View full text |Cite
|
Sign up to set email alerts
|

Use of Next Generation Sequencing to study two cowpox virus outbreaks

Abstract: Background Between 2008 and 2011 about 40 cases of human cowpox were reported from Germany and France. Infections had been acquired via close contact to infected, young pet rats. An identical and unique sequence of the hemagglutinin gene was found in various cowpox virus (CPXV) isolates pointing to a common source of infection. In a second CPXV outbreak in cats in a small animal clinic in Germany in 2015, four out of five hospitalized cats showed identical hemagglutinin sequences and thus, a hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…The scope of epidemiological modeling and game-theoretic cost analysis is wide. As cases of MPX become increasingly reported among humans (Antwerpen et al, 2019), we hope that the models may serve as a predictive tool to better study the spread of MPX.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of epidemiological modeling and game-theoretic cost analysis is wide. As cases of MPX become increasingly reported among humans (Antwerpen et al, 2019), we hope that the models may serve as a predictive tool to better study the spread of MPX.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of Cowpox virus as a single species was historically based on host specificity and phenotypic properties, e.g., formation of hemorrhagic pocks on infected chorioallantoic membranes (CAM) of eggs and electron microscopy-mediated identification of A-type inclusion bodies (ATI) [12,13,14]. Genome characterization was initially done by restriction fragment length polymorphism (RFLP) [15] and currently by high-throughput sequencing (HTS) of whole genomes [16,17]. Recent phylogenetic investigations using full-length genomes demonstrated that “ Cowpox virus ” is rather a polyphyletic group than a single species [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…As of now, 26 CPXV isolates possess K3 orthologs that are identical to CPXV-D 043/TATV 037 on the protein level. These viruses were mostly isolated from humans (38%), rats (31%) and cats (23%) [ 22 , 26 , 27 ], and PKR derived from these hosts were intermediately sensitive to this K3 ortholog. The host range of TATV, which was isolated from an apparently healthy gerbil ( Tatera kempi ), is unknown [ 28 ].…”
Section: Discussionmentioning
confidence: 99%